VIRTUAL TOUR BERBASIS E-PANORAMA SEBAGAI PENGENALAN KAMPUS UNIVERSITAS PENDIDIKAN MANDALIKA - Muhammad Fadil Salmansyah; Indriaturrahmi Indriaturrahmi; Raden Fanny Printi Ardi; Jarir Jarir (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
The rapid development of information technology has encouraged the emergence of digital innovations in various fields, one of which is Virtual Tour innovation. Undikma campus needs to have a visual promotional media that can describe the campus facilities and environment as a whole, and is easily accessible to prospective students and the wider community. Based on these problems, this research aims to build an E-Panorama-based Virtual Tour as a medium for introducing Undikma campus visually to prospective students and the public through a website that can be accessed by anyone. By utilizing 360-degree panoramic photos, this Virtual Tour is expected to provide an interactive visual experience for users and increase the attractiveness of Undikma campus for prospective students and the community. The development model used in this research is the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept, design, material collecting, assembly, testing, and distribution. Based on the results of the feasibility test, it shows that the Virtual Tour meets high standards with a feasibility percentage of 87 percent from media experts and 85.72 percent from users, so that this Virtual Tour can be declared suitable for use with a very good level of acceptance. So, it can be concluded from this research that the construction of the E-Panorama-based Virtual Tour has succeeded in achieving its goal as a medium for visually introducing the Undikma campus to prospective students and the public through a website that can be accessed by anyone and can be well received by users.